Pengaruh Attitude, Subjective Norms, Perceived behavior control dan Moral Norms Terhadap Purchase Intention Pakaian Thrift: Studi pada Generasi Z di Kota Malang - Okta Fajar Nuraini; Nur Laili Fikriah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of attitude, subjective norms, perceived behavior control, and moral norms on the purchase intention of thrift clothing for Generation Z in Malang City. This study uses a modified Theory of Planned Behavior (TPB) framework by adding moral norms variables. Data were collected through questionnaires distributed to 180 respondents using purposive sampling technique. The results of data analysis using the SmartPLS version 4.0 method show that subjective norms, perceived behavior control, and moral norms have a significant influence on purchase intention. In contrast, attitude does not show a significant effect. This finding suggests that social and moral norms play an important role in influencing purchase decisions, while the emotional, social, epistemic, and environmental value indicators of attitude are not strong enough to drive purchase intention. This study makes a theoretical contribution by reinforcing the relevance of the TPB in the context of thrift clothing purchases, as well as practical implications in the form of marketing strategies that focus on consumer education and strengthening social norms. Further research is recommended to explore the influence of social media and other factors relevant to Generation Z.